Why People Lead and Others Follow: The Black Perspective. Issue 7 (3rd October 2021) - Cosby, Robert L.; Berry Edwards, Janice
ABSTRACT: There are differences between Black and White leadership. Black leaders have overcome many obstacles simply to be given the opportunity to lead, often without the same tools and opportunities as their White counterparts. The evolution of Black leaders, whether called colored, Negro, Afro-American, Black, or BIPOC (Blacks, Indigenous, and People of Color) or Other speaks to how language and people have evolved to coalesce around issues of equality, equity, oppression, and polarization. This essay presents some leadership styles and provides some background on types of Black leaders and how they lead. From political leaders, to thought leaders, to religious leaders, the essay offers some reasons for Blacks' psychological thirst for healing and relief from the cumulative effects over time of persistently experiencing racism, and the retriggering of psychological trauma of slavery. The relentless battle of physiological pain and the psychological strain and the energy associated with racism can be overwhelming. Some Black leaders offer a "we-ness" of intrapsychic relief that provides a vision of hope for many in the African American community. The essay concludes with positions that recent Black leaders have taken and what the future of Black leadership may be.